A Decade of Alcoholism Research A review of the research activities of the Alcoholism and Drug Addiction Research Foundation of Ontario, 1951-1961 - Popham, Robert E.; Schmidt, Wolfgang (Heritage, 2019)
The year 1961 marked the beginning of the second decade of operation of the Alcoholism Research Foundation of Ontario. It also marked the end, in certain respects, of a stage in its development as a research organization. The most concrete event in this regard was an amendment to the act governing the Foundation, which added the words 'Drug Addiction' to its name and broadened its legitimate scope to include the study of virtually all forms of addictive behaviour. The year appeared to mark the end of a formative and largely exploratory stage of research and the beginning of a period characterized by a more precise sense of overall direction. This is best revealed through an examination of the history of the Foundation's research endeavour and of the character and results of the numerous projects which have been conducted under its auspices. Such an examination was attempted in the research section of the 1961 Annual Report of the Foundation. However, because of the special purpose and highly restricted readership for which this report was designed, it seemed desirable to publish the material subsequently in a form suitable for wider distribution. Accordingly, the present volume was prepared, and comprises a somewhat revised and expanded version of the original review. It is hoped that it will prove of value not only to research workers but also to those whose primary responsibilities in the alcoholism field are in the realm of treatment, education, or the administration of programs with these functions